2016
DOI: 10.1177/1060028016639318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SSRIs and SNRIs on Nocturnal Urinary Frequency

Abstract: SSRI/SNRI agents as a combined group do not appear to have a significant impact on nocturnal urinary frequency. The SSRIs and SNRIs may have an opposite effect on nocturnal frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In contrast, peripheral serotonin, through stimulation of bladder 5-HT 2 , 5-HT 4 , and 5-HT 7 serotonin receptors, may promote detrusor contraction and facilitate micturition [51,52]. From this perspective, the results of the present and previous studies [49,50] may reflect peripheral rather than central serotonergic control of micturition. It is possible that in some patients treated with SSRI antidepressants increased serotonin levels and stimulation of specific 5-HT receptors in the bladder enhance SUI symptoms.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…In contrast, peripheral serotonin, through stimulation of bladder 5-HT 2 , 5-HT 4 , and 5-HT 7 serotonin receptors, may promote detrusor contraction and facilitate micturition [51,52]. From this perspective, the results of the present and previous studies [49,50] may reflect peripheral rather than central serotonergic control of micturition. It is possible that in some patients treated with SSRI antidepressants increased serotonin levels and stimulation of specific 5-HT receptors in the bladder enhance SUI symptoms.…”
Section: Discussionmentioning
confidence: 46%
“…In a cross-sectional, population-based study based on mailed questionnaires, Felde et al [49] found that the use of antidepressants, but not anxiolytics, was associated with a general risk of urinary incontinence. A study of psychiatric patients [50] undergoing nocturnal polysomnography in a sleep center revealed that treatment with the SSRI drug, sertraline, increased nocturnal urinary frequency as compared to the serotonin-noradrenaline reuptake inhibitor (SNRI), duloxetine. The difference between sertraline and duloxetine could reflect a class effect, with SSRI antidepressants increasing and SNRI antidepressants decreasing nocturnal urinary frequency [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of antidepressants can result in disparate prevalence of nocturia. One study reported a divergent result of nocturnal urinary frequency between those on SSRIs and those on noradrenaline reuptake inhibitors (NRI), with patients on SSRI reporting higher nocturnal urinary frequency than did those on NRI [71]. Moreover, compared with duloxetine, frequency increased 3-fold in the sertraline group [71].…”
Section: Depression: Relationship To Nocturia Sleep and Osamentioning
confidence: 99%
“…One study reported a divergent result of nocturnal urinary frequency between those on SSRIs and those on noradrenaline reuptake inhibitors (NRI), with patients on SSRI reporting higher nocturnal urinary frequency than did those on NRI [71]. Moreover, compared with duloxetine, frequency increased 3-fold in the sertraline group [71]. These results arise from different drugs and side-effect profiles, but because nocturia increases depression and affects sleep quality in depressed patients, it is advisable to keep close surveillance of symptoms of nocturia in patients with depression.…”
Section: Depression: Relationship To Nocturia Sleep and Osamentioning
confidence: 99%